Acid-base balance in sheep with experimentally induced acute ruminal lactic acidosis - Sabes, A. F. [UNESP]; Girardi, A. M. [UNESP]; Filho, D.Zangirolami [UNESP]; Bueno, G. M. [UNESP]; Oliveira, J. A. [UNESP]; Marques, L. C. [UNESP] (FapUNIFESP (SciELO), 2017)
This study aimed to investigate the changes in the acid-base balance of sheep with experimentally induced acute ruminal lactic acidosis (ARA). Ten ewes orally received 15 grams of sucrose per kilogram of body mass. Arterial blood samples for blood gas analysis were obtained at the following intervals: before the induction of ARA (control), and 2, 4, 6, 8, 10, 12, 16, 20, 24, 28, 32, 36, 48, 72, 96, 120 and 144 hours after sucrose administration. Urine samples for pH measurement were obtained at the following times: -15 days, -7 days, and immediately before sucrose administration, then at 24, 48, 72, 96, 120 and 144 hours. Thereafter, both blood and urine samples were obtained on the 2nd, 3rd, and 4th following weeks. From 4 hours after the induction, elevation of the pH, bicarbonate and base excess on the arterial blood was observed. After 12 hours, the animals showed a decrease of these parameters, as well as urine acidification, which are symptomatic of metabolic acidosis. Within 28 hours, all parameters were normalized except the base excess, which only returned to normal after 72 hours. Despite the occurrence of acidemia, there was no need for medication and no animals died.
Keywords: Blood gas analysis; Metabolic acidosis; Santa inês